1999
DOI: 10.1093/clinchem/45.12.2243
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Cystatin C after Renal Transplantation and Acute Rejection in Adults

Abstract: Background: Cystatin C has recently been proposed as an alternative marker of glomerular filtration rate. The diagnostic value of plasma cystatin C for the longitudinal assessment of kidney function after renal transplantation, however, has not been addressed. Methods: Renal function was evaluated in 30 adults receiving renal transplants (46 ± 9 years, mean ± SD) and in 56 healthy controls (38 ± 10 years) using cystatin C. Plasma cystatin C was determined daily starting the day of surgery and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…In renal transplant patients, serum CysC concentrations paralleled those of creatinine regardless of graft function (absence or presence of DGF). Consequently, serum CysC and creatinine signifi cantly correlated over the postoperative study period as observed previously in adult renal transplant patients [31] and subjects suffering from chronic renal disease [13]. Some differences, however, were apparent in their respective serum kinetics.…”
Section: Discusionsupporting
confidence: 74%
See 1 more Smart Citation
“…In renal transplant patients, serum CysC concentrations paralleled those of creatinine regardless of graft function (absence or presence of DGF). Consequently, serum CysC and creatinine signifi cantly correlated over the postoperative study period as observed previously in adult renal transplant patients [31] and subjects suffering from chronic renal disease [13]. Some differences, however, were apparent in their respective serum kinetics.…”
Section: Discusionsupporting
confidence: 74%
“…Earlier detection of renal damage may lead to more effective intervention. In a preliminary study, LeBricon et al [13] fi rst suggested that CysC was more sensitive than SCr for detecting decreases in GFR and delayed graft function in renal transplant patients. As in most studies, serum CysC measurements correlated well with SCr and creatinine clearance (CrCl).…”
mentioning
confidence: 99%
“…Plasma markers for glomerular filtration have been investigated in kidney transplant recipients. Cystatin‐C is an example of a promising marker for glomerular filtration rate (15,16). Calcineurin‐free immunosuppressive therapy in renal transplantation has been associated with better short‐term renal function (17).…”
Section: Surrogate Markersmentioning
confidence: 99%
“…Estimation of cystatin C is an alternative marker for evaluating renal function. Cystatin C has been compared with serum creatinine and creatinine clearance in renal transplant recipients (25). Plasma cystatin C correlates with plasma creatinine (r = 0.741, p < 0.0001) and creatinine clearance (r = 0.882, p < 0.001).…”
Section: Clinical Endpointsmentioning
confidence: 99%